The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.05.14.095406
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rational Design of Minimal Synthetic Promoters for Plants

Abstract: Promoters serve a critical role in establishing baseline transcriptional capacity through the recruitment of proteins, including transcription factors (TFs). Previously, a paucity of data for cis-regulatory elements in plants meant that it was challenging to determine which sequence elements in plant promoter sequences contributed to transcriptional function. In this study, we have identified functional elements in the promoters of plant genes and plant pathogens that utilise plant transcriptional machinery fo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Appropriate gene expression is the critical function of a nucleus, and understanding how gene regulatory networks control transcription has become a major focus in a variety of fields, from medicine to plant breeding. Owing to the massive output of information from next-generation sequencing, CREs have been identified as key players in gene transcription, and even small mutations in these regions have been shown to cause dramatic changes in phenotype (Cai et al, 2020;Rodr ıguez-Leal et al, 2017). These regulatory elements represent an exciting new area of exploration in which levels of gene product can be controlled with high sensitivity, without affecting the coding sequence of the gene or needing to introduce RNA to a cell, as with RNAi, and are ideal sequences to be modified by CRISPR/Cas9 mediated genome editing techniques to achieve fine tuning of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate gene expression is the critical function of a nucleus, and understanding how gene regulatory networks control transcription has become a major focus in a variety of fields, from medicine to plant breeding. Owing to the massive output of information from next-generation sequencing, CREs have been identified as key players in gene transcription, and even small mutations in these regions have been shown to cause dramatic changes in phenotype (Cai et al, 2020;Rodr ıguez-Leal et al, 2017). These regulatory elements represent an exciting new area of exploration in which levels of gene product can be controlled with high sensitivity, without affecting the coding sequence of the gene or needing to introduce RNA to a cell, as with RNAi, and are ideal sequences to be modified by CRISPR/Cas9 mediated genome editing techniques to achieve fine tuning of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the basic gene construct design has largely included synthetic sequences upstream of a core promoter sequence such as the −46 35S promoter. Recently, a minimal synthetic promoter was designed for constitutive response by various arrangement of CREs at different positions to TATA box area (Cai et al ., 2020). In our study, no downstream gene expression was observed in synthetic promoters including three copies of single CREs (Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…However, when applied to genome-scale collections of TFs, insufficient expression was obtained for several hundred proteins (91). We expressed TGA TFs, known to regulate expression of defence related genes (93-97) as well as the CaMV 35s promoter (74,(98)(99)(100)(101)(102). We also expressed wheat homologues of TFs that regulate circadian rhythms in Arabidopsis including homeologues of LUX ARRHYTHMO (LUX) from each of the three wheat sub-genomes (103).…”
Section: Discussionmentioning
confidence: 99%